1970
DOI: 10.1111/j.1365-2672.1970.tb05245.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Proteinases Excreted by Bacillus subtilis Marburg Strain during Sporulation

Abstract: Summary. This study has characterized 3 proteolytic enzymes during sporulation by Bacillus subtilis Marburg strain when grown in nutrient broth. A method of purification is described which permits the separation of 2 different proteinases: one belonging to the metal enzyme group and the other to the serine enzyme group. The third enzyme, probably an esterase, showed a high esterolytic activity, but only low proteolytic activity. Determination of the 3 enzymes in a mixture was accomplished by using specific su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
1

Year Published

1973
1973
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(91 citation statements)
references
References 22 publications
1
89
0
1
Order By: Relevance
“…The accumulation of serine and metal proteolytic activities in the culture supernatant fraction, an early sporulation event (1,7,(13)(14)(15), occurred with a similar time course in mutant and wild-type cells at 350 and 460 (Fig. 3).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The accumulation of serine and metal proteolytic activities in the culture supernatant fraction, an early sporulation event (1,7,(13)(14)(15), occurred with a similar time course in mutant and wild-type cells at 350 and 460 (Fig. 3).…”
Section: Resultsmentioning
confidence: 96%
“…3). As judged by appropriate inhibitor experiments, at any given time 75% of the azocasein activity was due to serine protease and 25% of the activity was due to to metal protease (14). The mutant cells slightly underproduced both enzymes at 35°and 460.…”
Section: Resultsmentioning
confidence: 99%
“…In a survey of enzymes produced by P. acnes and related bacteria, Hoeffler (1 977) showed that 73 yo of P. acnes, 18 yo of P. avidum and 33 yo of P. granulosum strains tested produced hyaluronidase. Puhvel & Reisner (1972) have shown that isolates of P. acnes from both normal skin and the skin of patients with cystic acne produce the enzyme in vitro. The pH optima and temperature stability of the enzymes from the various isolates were described in preparations of crude exocellular products, but no attempt was made to purify or characterize the enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…3 were prepared from cells at the early stationary phase of growth. At that time point the level of OmpA protein was near its maximum (to be shown in detail elsewhere) and the amount of exoproteases, which appear during the stationary phase, was still very small (Millet, 1970;M. Sibakov, personal communication).…”
Section: Resultsmentioning
confidence: 99%